Trichodesmium counts and environmental data at TRIAXUS events M153_19-3 and M153_56-2 during RV Meteor cruise in 2019 - Bettina Martin; Rolf Koppelmann (PANGAEA, 2024)
The TRIAXUS ROTV (Remotely Operated Towed Vehicle, MacArtney) is a towed and undulating system which is equipped with a SEABIRD FASTCAT, SBE 49, AANDERAA OXYGEN OPTODE 4330 F, a SEASCAN SUNADeep Nitrate Sensor, a Turner Chl a sensor and a Seascan Video Plankton Recorder (VPR). It measures: seawater temperatures, salinity, dissolved oxygen, nitrate concentrations, Chlorophyll a in the water column. The Videoplanktonrecorder detects particles and organisms in the water column. Trichodesmium colonies were identified using a deep learning software.